Choline chloride–zinc chloride ionic liquid as a green template for the sol–gel synthesis of mesoporous titania. Issue 17 (6th February 2017) - Preethi, T.; Padmapriya, M. P.; Abarna, B.; Rajarajeswari, G. R.
Abstract : Choline chloride–zinc chloride ionic liquid has been used as a green template to synthesis highly crystalline mesoporou anatase titania. Abstract : Utilization of organic templates for the synthesis of structure- and morphology-controlled solids is being researched extensively. Use of green templates provides advantages in the form of easy processability and less toxicity compared to conventional chemical templates, in addition to customizable mesoporous network structures in solids. In this regard, the present work aimed at assessing the influence of choline chloride–zinc chloride ionic liquid (IL) in controlling the crystallite characteristics and improving the surface properties of sol–gel derived nanotitania. Thermal, surface area, porosity, crystallinity, chemical composition, textural and morphological characterizations of the IL templated titania are described in the present work. XRD results showed that all IL templated titania samples possessed anatase structure. The sample prepared using 2 mL of IL with 9 mL of titanium tetraisopropoxide (ILT-2) possessed uniformly dispersed, spherical particles with an average particle size of 13.2 nm and a surface area of 75.1 m 2 g −1 . A moderate red shift of the absorption profile of titania was also observed. Among the synthesized samples, ILT-2 exhibited the highest photocatalytic activity for the degradation of 4-chlorophenol under UV irradiation. The ability of the choline chloride–zinc chloride IL to offer very good control over the growth of titania particles together with its easy removal make it a potential green template for the sol–gel synthesis of mesoporous solids.